Reduced White Matter Integrity in Patients With End-Stage and Non-end-Stage Chronic Kidney Disease: A Tract-Based Spatial Statistics Study - Jiang, Yuhan; Gao, Qiuyi; Liu, Yangyingqiu; Gao, Bingbing; Che, Yiwei; Lin, Liangjie; Jiang, Jian; Chang, Peipei; Song, Qingwei; Wang, Weiwei; Wang, Nan; Miao, Yanwei (Frontiers in Human Neuroscience, 2021)
Background and purpose: Reduced white matter integrity has been implicated in chronic kidney disease (CKD), especially in end-stage renal disease (ESRD). However, whether the differences in white matter abnormalities exist in ESRD and non-end-stage CKD (NES-CKD) remains unclear. Hence, this study aimed to investigate the white matter microstructural changes between the two stages using diffusion tensor imaging (DTI) and explore the related influencing factors. Methods: DTI images were prospectively acquired from 18 ESRD patients, 22 NES-CKD patients and 19 healthy controls (HCs). Tract-based spatial statistics (TBSS) was performed to assess the voxel-wise differences in white matter abnormalities among the three groups. The relationships between DTI parameters and biochemical data were also analyzed. Results: Compared with NES-CKDs, FA value was significantly decreased and AD value increased in ESRDs mainly in brain regions of bilateral anterior thalamic radiation, the genu and body of corpus callosum, bilateral anterior corona radiata, superior corona radiata, and superior longitudinal fasciculus. Besides, extensive and symmetrical deep white matter damages were observed in ESRD patients, accompanied by increased MD and RD values. Multiple regression analysis revealed that uric acid and serum phosphorus level can be used as independent predictors of white matter microstructural abnormalities in clusters with statistical differences in DTI parameters between ESRD and NES-CKD groups. Conclusions: In the progression of CKD, ESRD patients have more severe white matter microstructural abnormalities than NES-CKDs, and this progressive deterioration may be related to uric acid and phosphate levels.